The triple-phase response--problems of water balance after pituitary surgery. - Lindsay, R. S. (BMJ Group, 1995)
A 29-year-old woman presenting with persistent headache and oligomenorrhoea was found to have a pituitary adenoma which was treated surgically. Postoperatively she developed diabetes insipidus which resolved on treatment with desmopressin acetate. She represented 11 days post surgery with nausea and vomiting and inappropriate antidiuresis was diagnosed in an infectious diseases unit. On re-admission to our unit cranial diabetes insipidus was confirmed by water deprivation. This case demonstrates the need for careful monitoring of patients after pituitary and suprasellar surgery or head injury.